2017
DOI: 10.1016/j.saa.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring wheat mitochondrial compositional and respiratory changes using Fourier transform mid-infrared spectroscopy in response to agrochemical treatments

Abstract: Fungicides and plant growth regulators can impact plant growth outside of their effects on fungal pathogens. Although many of these chemicals are inhibitors of mitochondrial oxygen uptake, information remains limited as to whether they are able to modify other mitochondrial constituents. Fourier transform mid-infrared spectroscopy (FT-mIR) offers a high sample throughput method to comparatively and qualitatively evaluate the effects of exogenously added compounds on mitochondrial components. Therefore the obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In another word, strobilurins act on fungal mitochondrial respiration, causing electron transport blockage in the cytochrome bc1 complex (complex III of electron transport chain), between cytochrome b and cytochrome c1, at the Qo site By inhibiting ubiquinol-cytochrome c-oxide reductase, they reduce the respiratory process blocking the fungus cell's energy supply (ATP), leading to its death, thus, they are also known as QoIs or inhibitors of the bc1 complex [10,20]. Because this complex is present in all eukaryotic organisms, there is at least partial inhibition of electron transport in plants when they come in contact with strobilurins such as pyraclostrobin and azoxystrobin which isolated from mitochondria in wheat plants [22].…”
Section: The Fungicidal Action Of Strobilurinsmentioning
confidence: 99%
“…In another word, strobilurins act on fungal mitochondrial respiration, causing electron transport blockage in the cytochrome bc1 complex (complex III of electron transport chain), between cytochrome b and cytochrome c1, at the Qo site By inhibiting ubiquinol-cytochrome c-oxide reductase, they reduce the respiratory process blocking the fungus cell's energy supply (ATP), leading to its death, thus, they are also known as QoIs or inhibitors of the bc1 complex [10,20]. Because this complex is present in all eukaryotic organisms, there is at least partial inhibition of electron transport in plants when they come in contact with strobilurins such as pyraclostrobin and azoxystrobin which isolated from mitochondria in wheat plants [22].…”
Section: The Fungicidal Action Of Strobilurinsmentioning
confidence: 99%
“…[ 13 , 14 ]. It mainly inhibits the electron transfer between cytochrome b and c1 in mitochondrial respiration of pathogenic cells, so that mitochondria cannot normally provide the required energy for cell metabolism, thereby achieving a bactericidal effect [ 15 , 16 , 17 ]. In a previous report from our research group, Wu et al [ 18 ] found that 30% pyraclostrobin SC could effectively control powdery mildew with a control efficacy of more than 90%, and notably promote its yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Amisulbrom (AML), a sulfonamide fungicide, is registered for foliar applications on grape, potatoes and other crops [1,2]. Isoflucypram (ISO) is one of new succinate dehydrogenase inhibitor (SDHI) fungicides that are used for fungi and mould control [3].…”
Section: Introductionmentioning
confidence: 99%